THE RELATIONSHIP BETWEEN THE LENGTH OF FEVER AND THE NUMBER OF LEUKOCYTES ON THE RESULTS OF TUBEX TF EXAMINATION IN TYPHOID FEVER PATIENTS - Diah Lestari; Tika Melani; Retno Martini Widhyasih (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Typhoid fever is a systemic disease caused by Salmonella typhi bacteria with LPS-09 antigens that can stimulate an immune response in the form of IgM antibodies, so it can be detected through Tubex TF and leukocyte counts as predictors to reduce morbidity and mortality. This study aims to determine the relationship between fever duration and leukocyte count based on Tubex TF examination results in diagnosing typhoid fever. The type of research used was associative analytical observational with secondary data from 70 typhoid fever patients at Pasar Rebo Hospital from March 2023 to February 2024. The results showed that most patients were female (41 or 58.6%) and the largest age group was children (6-11 years) with 20 patients (28.6%). Based on the Fisher’s Exact test, there was a significant association between fever duration and Tubex TF result (p=0.000), while there was no association between leucocyte count and Tubex TF result (p=0.645). In conclusion, fever duration can be used as an indicator in the diagnosis of typhoid fever with Tubex TF, while leucocyte count cannot always be used as a specific marker. These results are expected to improve individual health information of typhoid fever patients through early detection and intervention.